Challenges facing teacher education in Qatar: Q methodology research. Issue 7 (July 2022) - Alkhateeb, Hadeel; Romanowski, Michael H.; Sellami, Abdellatif; Abu-Tineh, Abdullah M.; Chaaban, Youmen
Abstract: This study aims to identify the challenges facing teacher education in Qatar. Through Q methodology, it examines the ways in which schoolteachers, preservice teachers, teacher education faculty, and Ministry of Education and Higher Education personnel identify what they see as significant challenges faced by teacher education in the country. The overall aim is to provide an overview of teacher education in Qatar and the challenges of improving programs and processes. Results show that the participants' perspectives fall on a continuum of diverse views in which minimal consensus exists. Still, four consensus points were found across the emerged perspectives: schoolteachers' workload, responsibilities and roles of educational stakeholders, the exasperation towards college-based teacher education, and the impact of culture on teacher education. Based on the results of this study, we argue that these consensus points represent the main challenges facing teacher education in Qatar. Abstract : Teacher education; Teacher challenges; Q-methodology; Qatar.